IgE as a predictor to omalizumab response in patients with chronic spontaneous urticaria - Ensina, Luis Felipe; Brandão, Larissa; Arruda, Luisa Karla; Sarquis Serpa, Faradiba; Campos, Régis Albuquerque; Valle, Solange Rodrigues Oliveira; Criado, Paulo Ricardo; Saini, Sarbjit Singh; Criado, Roberta Fachini Jardim (Frontiers in Allergy, 2025)
This multicenter study aimed to explore whether baseline total immunoglobulin E (IgE) levels could predict omalizumab response in chronic spontaneous urticaria (CSU) patients. Refractory CSU patients, treated with omalizumab after failing second-generation H1-antihistamines, were analyzed retrospectively across seven centers in Brazil. The study assessed total IgE levels at baseline, comparing responders to non-responders and considering complete and partial responses. The results showed a significant reduction in CSU symptoms post-treatment. Non-responders had lower baseline IgE levels. A sensitivity of 67.8% and specificity of 93.3% for predicting a response were found at an IgE level of 59.5 IU/ml. Similar values were observed for complete responders. Notably, a baseline IgE level lower than 59.5 IU/ml may indicate late responders. The study underscores the potential of baseline IgE levels as a predictive biomarker for omalizumab response in CSU patients. Further research, incorporating diverse populations and analyzing response variables, is warranted to validate these findings.